Developing a health interview tool for Medicaid home and community-based services clients and home care aides through a community-engaged approach. Issue 1 (2nd January 2019) - Johnson, Rebecca; Diaz, Laura; Boyken, Lara; Saberbein, Gustavo; Rogers, Beverly; Smith, Pauline; Rodriguez, Lillybeth; Danilovich, Margaret
ABSTRACT: We describe a community-engaged approach to develop and pilot a home care aide (HCA) administered health interview with Medicaid Home and Community-based Services clients. Stakeholders identified five priority health topics and selected a card sorting methodology for interviews. A barrier to interviewing clients was decreased communication skills among HCAs, and we modified health interview training to include communication training. Stakeholders reported the interview methodology was feasible within usual care, acceptable to clients, and contributed to increased knowledge on providing person-centered care. Stakeholder engagement resulted in valuable insights regarding the health interview methodology and relevant training needs.